Cognitive Behavioral Therapy and Pharmacotherapy for the Treatment of Tobacco Use Disorder in Primary Care for Resident Physicians - Juhee C. McDougal; Shin Ock; Lindsay B. Demers; Robert L. Sokolove (Association of American Medical Colleges, 2019)
Introduction Though the prevalence of smoking has decreased, it remains the second leading risk for early death and disability worldwide. At the primary care level, the combined use of behavioral interventions and pharmacotherapy has been shown to be more effective in reduction of smoking. Among behavioral interventions, cognitive behavioral therapy (CBT) provides a useful framework for helping patients quit smoking. Methods This 90-minute workshop was led by two facilitators, a general internist who practices as a primary care physician and a clinical psychologist with content expertise in CBT. This pairing provided complementary perspectives to allow for learner engagement. To evaluate the workshop, we used a pre-/postsurvey that was administered at the beginning and the end of the workshop. Participants were asked how often they incorporated (presurvey) and intended to incorporate (postsurvey) CBT as part of smoking cessation counseling in their clinical practices. Results There was a statistically significant change in learners' perceived usefulness of CBT for smoking cessation from pre- to postworkshop. Discussion Our workshop is a unique contribution to the literature. Limitations of our study include not knowing the long-term effect of knowledge acquisition or decay. Our future direction will be to produce training that applies CBT to other common chronic diseases that have a huge behavioral component in primary care, such as insomnia, chronic pain, and obesity.